1, 3, 6, 8-pyrene sulfonic acid tetrasodium fluorescent pigment synthesis and security ink production - Arman Kandirmaz, Emine; Ozcan, Arif (Journal of Graphic Engineering and Design, 2024)
Colorants used in security inks are special pigments that radiate in the UV region or IR region. Obtained pigments can be from valuable rare earth elements or they can be organic based. Organic-based pigments are generally insoluble in water, which limits their use. For this purpose, an organic based UV-radiating pigment was synthesized and made water-soluble by forming its salt. With the obtained salt-formed pigment, inkjet ink that can be used in counterfeiting was applied and its printability and resistance properties were determined. In this study, 1, 3, 6, 8-pyrene sulfonic acid tetrasodium salt was synthesized and water-based inkjet inks with hydroxy ethyl cellulose binder were produced. The prepared inks were printed on the paper surface. The color and gloss of the prints obtained were measured both in the visible region and in the UV region. Its optical properties were detected by UV spectroscopy. Strength properties such as light fastness, nitro resistance, alkali resistance, acid resistance, rub resistance, drying time, adhesion and dry film weight of the prints were determined. As a result; Inkjet ink with 1, 3, 6, 8-pyrene sulfonic acid tetrasodium salt was produced and it was concluded that it has good resistance properties. Article history: Received (June 16, 2023); Revised (September 22, 2023); Accepted (October 3, 2023); Published online (September 1, 2024)